Nilai Pendidikan Karakter Al-Qur’an Surat Ali-Imran Ayat 102-104 Pada Kurikulum Darul Arqam Dasar (DAD) Ikatan Mahasiswa Muhammadiyah (IMM) - Dhian Wahana Putra (Universitas Muhammadiyah Jember, 2019)
This study examines values of character education as stated in QS. Ali-Imran verses 102-104 included in the curriculum of Darul Arqam Dasar for Muhammadiyah Student Association (MSA). It should be emphasized that MSA is one of autonomous Muhammadiyah organizations with noble duties and responsibilities. The glory of these responsibilities may be traced through the objectives of MSA—namely: